The Hidden Influence and Catalysts of Religious and Moral Education in Ghanaian Basic Schools: Co-Curricular Activities in Perspective - Dennis Tawiah; John Kwaku Opoku; Peter Addai-Mensah (E-Journal of Humanities, Arts and Social Sciences)
This study investigates the hidden influences and catalysts of Religious and Moral Education (RME) within co-curricular activities in Ghanaian basic schools. The importance of RME in Ghana’s educational system is undeniable, yet the issues of immoral behaviour among students persist, raising concerns about the efficacy of current educational methods. While formal classroom instruction is crucial, the impact of co-curricular activities on moral and religious development is less understood. This study uses a descriptive survey design to explore the practical factors that influence RME through co-curricular activities. Data were collected from 104 participants, including parents, teachers, and students from the Sefwi Wiawso Municipality. Findings indicate that co-curricular activities, such as community service, sports, debates, and cultural events, are essential for moral and religious growth. The study highlights the benefits of co-curricular activities, including the development of empathy, tolerance, leadership skills, and ethical decision-making. Despite these benefits, challenges such as limited resources, inadequate logistic support, and stakeholder disinterest hinder effective implementation. Parents feel excluded and desire more involvement and communication from schools. Teachers emphasize the value of these activities for reinforcing social and cultural values. The study concludes that integrating co-curricular activities into the curriculum is essential for fostering moral and religious development. These insights aim to guide policymakers and educators in improving RME programmes in Ghanaian basic schools, holistic growth of students. This study contributes to scholarship by highlighting the significant role of co-curricular activities in moral and religious education and suggesting practical improvements for educational policy and practice.